PEMANFAATAN AHP SEBAGAI MODEL SISTEM PENDUKUNG KEPUTUSAN SELEKSI PENERIMAAN KARYAWAN - Satriawaty Mallu1 (P3M STMIK Profesional Makassar, 2013)
Abstract: The use of AHP as a Decision Support System Model Employee Recruitment Selection. The system was developed and built using the Microsoft Access and Visual Basic. Decision-making to determine whether the applicant is accepted or not based on some criteria set by the company. This study aims to assist HR manager in recruitment selection process in deciding which applicants will be accepted as an employee of the company by applying AHP model. Manager of comparing the value of the interests of test criteria, applying the pairwise comparison matrix in order to obtain the weight for each criterion criteria both local and global criteria. The decision to determine which applicants will be accepted as an employee of the company to determine the viability of the company itself, so that the necessary decisions right in the election, so that corporate objectives can be achieved. Selection decision support system applications hiring managers can use human resources to help determine which candidates will be accepted.